Vom Einblick in die Buchrolle des himmlischen Thronsaals - Bergmeier, Roland (Biblische Zeitschrift, 2020)
The following article is trying to prove that the most fitting background for the use of the ἀρνίον-metaphor, that is first introduced in Rev 5 in a special connection with the heavenly scroll, may be the hellenistic knowledge of the story of the lamb’s prophecy in the Demotic papyrus about “the Lamb to Bocchoris”. So it is by loosing the seven seals of the heavenly scroll that the Lamb of the Apocalypse prophecies what soon will happen. When the Lamb has broken open the first seal, the first rider on a white horse opens the future eschatological drama that proleptically culminates in the last judgement wrath of the Lamb (6:16), taken up again by the rider on the white horse in Rev 19.